Technology Acceptance and Future of Internet Banking in Vietnam - Duc Toan Le; Huu Phu Nguyen; Van Nhan Ho; Thi Phi Yen Ho; Quang Tam Nguyen; Nguyen Ngoc Anh Le (Foresight and STI Governance)
The technology acceptance model (TAM) has long been applied to investigate consumer attitudes towards novel solutions and identify incentives that increase their willingness to adopt them. A cumulative tradition has already been developed in this stream of research. Using a modified TAM model, the authors explore factors that affect the intention of Vietnamese banks and their clients to adopt internet banking services. Currently, there is a number of factors hindering the diffusion of internet banking, particularly the underdevelopment of the technological infrastructure, the lack of investment, and the habits of the majority of providers and consumers of services to interact via traditional formats. The study finds out that the adoption of internet banking could be encouraged by perceived usefulness, perceived ease of use, and, finally customer satisfaction. Among the important factors to ensure these conditions are an advanced customer support system, user-friendly interface, promptness of services, and transparency of banking operations. Among the recommendations put forward by the authors, special attention is given to the requirements for the skills of bank personnel, the need for continuous training, and the establishment of targeted strategic indicators at the public level that facilitate the embeddedness of internet banking in the life of Vietnamese society.